PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR MATA PELAJARAN ALAT UKUR SMK MUHAMMADIYAH 1 IMOGIRI TAHUN AJARAN 2014/2015 - Saleh Saleh; Samsul Hadi (Jurnal Taman Vokasi, 2015)
The general objective of this research is to know the improvement of the activity and achievement study of measuring instrument subject for tenth grade TKR 4th Students of SMK Muhammadiyah 1 Imogiri in Academic Year 2014/2015. The hypothesis of this research is the model of cooperative learning type NHT to be able to improve the activity and achievement study of measuring instrument subject for tenth grade TKR 4th students of SMK Muhammadiyah 1 Imogiri in Academic Year 2014/2015. The type of this research is a classroom action research which done by cooperative learning. The subject of this research is the tenth grade TKR 4th students of SMK Muhammadiyah 1 Imogiri which consists of 35 students. The object of this research is students’ activity and achievement study which got from the implementation model of cooperative learning type NHT. This research is conducted 3 cycle by using technique of collecting the data which conducted through test, observation, and documentation. Technical data analyst for observation sheet and achievement test data analyzed quantitative description with statistical formula. results of using the type Cooperative Learning Model Numbered Head Together (NHT) had showed an improvement in learning achievement and activity of the tenth grade students of SMK Muhammadiyah 1 TKR 4 Imogiri on Subjects of each cycle the measuring instrument. It is evidenced by an improvement in the average yield observation sheet activeness percentage of students in the first cycle of 44.14%  and an improvement  in the second cycle of 17.43% to 61.57% and in the third cycle improved by 21.29% to 82.86%. otherwise it is based on achievement test on the first cycle the average value obtained pre-test 60.71 and the average value of post test 69.57 so that student achievement increased by 8.86 and the second cycle of the average values obtained pre test 62.28 and the average value of post test 75.42 increased learning achievement tests of 13.14 and in the third cycle the average value of pre-test 65.14 and the average value of post test 83.42. So that student achievement increased by 18.28. It can be concluded that the model of cooperative learning can enhance the activity and students’ achievement.